Penerapan Model Latihan Daya Tahan Kardiovaskuler With The Ball Permainan Sepak Bola SSB BU Pratama - Adhis Sandika; Imam Mahfud (Journal of Physical Education, 2021)
This study discusses the cardiovascular endurance training model to increase the VO2max of soccer players. The aim of this cardio research is to determine cardiovascular improvement through the application of an endurance training model with soccer ball players aged 14-17 years. This research applies an experimental method using the One Group Pretest Posttest Design. The sample in this study was 30 Bintang Utara Star Pratama Soccer School’s players. A total of 30 players who were actively practicing and were not injured from all Bintang Utara Pratama Soccer School’s players. Based on the results of the study, which showed that the cardiovascular endurance training model with the soccer ball players was 0.00 0.05 then the control group got a significance value of 0.873 0.05, so it can be concluded that there was a significant effect on the experimental group. Keywords : Training, Cardiovaskuler, Soccer